Factors that Foster Teacher Educators’ Engagement in Technology Learning in the Workplace - Schols, Maurice (International Journal of Advanced Corporate Learning (iJAC), 2019)
New technologies are transforming every aspect of today’s education, and teacher educators, teacher education institutions and policy makers are universally underscoring the need for adequate technology professionalisation programs. However, traditional professional development opportunities still leave much to be desired because educators perceive most of workshops, training and off-campus days as being separate from engagement with authentic teaching contexts. We conducted this study to explore and identify factors that foster teacher educators engagement in technology learning. Fifteen teacher educators from three interdisciplinary teams at a Dutch teacher education institution volunteered to participate in this qualitative study. We gathered data through reflective reports, semi-structured interviews and field observations. We found four factors that fostered teacher educators’ engagement in technology learning and that are in line with the international engagement literature. The implications of the findings might contribute to teacher educators’ technology professional development on both an individual level and institutional level.